Pharmacoepidemiological and drug interaction analysis in the treatment of chronic renal and hepatic failure - O. V. Zhukova; D. S. Fokina; O. V. Ruina; M. V. Khazov (IRBIS LLC, 2023)
Objective: to perform pharmacoepidemiological and drug interaction analysis of pharmacotherapy for liver/kidney transplantation.Material and methods. The study was conducted on the basis of multidisciplinary hospital in Nizhny Novgorod, which provides both therapeutic and high-tech surgical care. The object of the study was medical records of 34 patients who had undergone pharmacotherapy for liver/kidney transplantation. We evaluated the particularly dangerous moderate interactions that pose the greatest risk to patient health using Drugs.com electronic resource. Pharmacoepidemiologic assessment was performed using the ATC/DDD methodology (anatomical therapeutic chemical (ATC) classification system - defined daily dose (DDD)) recommended by the World Health Organization. The "average bed occupancy per year" was calculated using DDD per 100 bed-days. ABC analysis was used to estimate the costs of drug groups in therapy for liver/kidney transplantation. Results. In most cases, the third generation cephalosporins were used in the therapy of liver/kidney transplant patients (55.56% of all prescriptions). Antimicrobial drugs were mostly prescribed as monotherapy (61.9%). There were 111 potential major (14.41%) and moderate (72.07%) interactions detected. The largest number of moderate type risks was associated with changes in blood pressure levels (in 23.75% of cases - possible decrease, in 10% - increase), 7.5% of cases were accompanied by headaches, 6.25% - by reduction of drug effectiveness. In antimicrobial therapy, two main interactions were found: moxifloxacin - tacrolimus (arrhythmia), and metipred - moxifloxacin (tendon dystrophy), which is 12.5% of all main interactions for 21 case histories. In the ABC analysis, immunosuppressants were in group A (cost share 85.8%). Tacrolimus accounted for the largest amount of consumption: number of defined daily doses (NDDD) per year was 532.27 mg, NDDD per 100 bed days reached 432.18 (the highest among all drugs).Conclusion. Pharmacoepidemiologic analysis allows us to systematize data on medication use. The choice of drugs in order to ensure safe and effective use of the registered drug interactions is facilitated by electronic databases.